An empirical investigation of relationship among transformational leadership, strategic agility and organizational performance in a developing economy - Alkandi, Ibrahim (Edelweiss Applied Science and Technology, 2025)
The purpose of this research is to explore the relationship between strategic agility and organizational performance through the mediating role of transformational leadership. A cross-sectional survey involving 380 senior managers working within various industrial sectors was conducted. The data were analyzed using factor analysis and construct correlation covariances; additionally, mediation analysis was performed using Stata 16 structural equation modeling. The results revealed a significant direct effect between strategic agility and organizational performance, a significant direct effect between strategic agility and transformational leadership, and a significant direct effect between transformational leadership and organizational performance. Furthermore, the study found a significant indirect mediation effect of transformational leadership on the relationship between strategic agility and organizational performance. This study advances our understanding of the relationship between these variables. It is the first comprehensive study analyzing these variables in the Saudi industrial sectors. Practical implications are provided for industrial managers to adapt to environmental changes. This research offers integrated insights and supports leaders’ decisions and their effective interactions with strategic agility capabilities to enhance performance and achieve sustainable businesses in turbulent economic times.